Underactuated Manipulator with Control Based on Variable Dynamic Properties of Joints - Bansevicius, R.; Sarkauskas, K. K.; Tolocka, R. T. (Elektronika ir Elektrotechnika, 2007)
The underactuated manipulators are ones which have more degrees of freedom than the number of actuators. They allow us to develop the simplest devices with reduced weight, cost and energy consumption. Challenge is in organizing the control of kinematic chain consisting of both passive and active links. This is achieved by utilizing the effect of dynamic coupling in the system. The underactuated manipulator with active materials (piezoacative material, electrorheological fluid) joints between active and passive links is proposed. This offers to use such joints for braking passive links and influencing their free motion. The control of such underactuated manipulator may be organized by PID controller application. Ill. 4, bibl. 9 (in English; summaries in English, Russian and Lithuanian).